Antifungal activity of Leptadenia reticulata Wight and Arn. aerial parts - M.K. Mishra; P Tiwari.; D.K Dash.; Rajesh.S. Jadon; G. Ghosh; B.B. Barik (International Journal of Phytomedicine, 2010)
The petroleum ether, chloroform, acetone, methanol and aqueous extracts of the aerial parts of Leptadenia reticulata Wight and Arn. (Asclepiadaceae) were studied for in vitro antifungal activity against Aspergillus flavus, Aspergillus ruantti, Candida tropicalis, Candida albicans, Trichodermata viride and Trichodermata koningii respectively. The methanolic extract exhibited prominent antifungal activity against all the selected strains. Minimum inhibitory concentration of the extracts was performed by broth dilution method and the zone of inhibition was studied by agar disc diffusion method at concentrations of 2, 5 and 10mg/ml in DMSO. Cotrimazole (25μg/ml) was used as reference control for antifungal studies. Results of MIC study revealed the antifungal activities of the extracts against the tested strains in between concentration ranges 50-400μg/ml. The present study indicates the potential usefulness of L. reticulata aerial parts as antifungal agent.